Higher Dispersion Measures of Conduction and Repolarization in Type 1 Compared to Non-type 1 Brugada Syndrome Patients: An Electrocardiographic Study From a Single Center - Tse, Gary; Li, Ka Hou Christien; Li, Guangping; Liu, Tong; Bazoukis, George; Wong, Wing Tak; Chan, Matthew T. V.; Wong, Martin C. S.; Xia, Yunlong; Letsas, Konstantinos P.; Chan, Gary Chin Pang; Chan, Yat Sun; et al. (Frontiers in Cardiovascular Medicine, 2018)
Background: Brugada syndrome (BrS) is a cardiac ion channelopathy that predisposes affected individuals to sudden cardiac death. Type 1 BrS is thought to take a more malignant clinical course than non-type 1 BrS. We hypothesized that the degrees of abnormal repolarization and conduction are greater in type 1 subjects and these differences can be detected by electrocardiography (ECG). Methods: Electrocardiographic data from spontaneous type 1 and non-type 1 BrS patients were analyzed. ECG parameters were measured from leads V1 to V3. Values were expressed as median [lower quartile-upper quartile] and compared using Kruskal-Wallis ANOVA. Results: Compared to non-type 1 BrS patients (n=29), patients with spontaneous type 1 patterns (n=22) showed similar (P>0.05) heart rate (73 [64-77] vs. 68 [62-80] bpm), QRS duration (136 [124-161] vs. 127 [117-144] ms), uncorrected QT (418 [393-443] vs. 402 [386-424] ms) and corrected QT intervals (457 [414-474] vs. 430 [417-457] ms), JTpeak intervals (174 [144-183] vs. 174 [150-188] ms), Tpeak - Tend intervals (101 [93-120] vs. 99 [90-105] ms), Tpeak - Tend/QT ratios (0.25 [0.23-0.27] vs. 0.24 [0.22-0.27]), Tpeak - Tend/QRS (0.77 [0.62-0.87] vs. 0.77 [0.69-0.86]), Tpeak - Tend/(QRS x QT) (0.00074 [0.00034-0.00096] vs. 0.00073 [0.00048-0.00012] ms-1), index of Cardiac Electrophysiological Balance (iCEB, QT/QRS, marker of wavelength: 3.14 [2.56-3.35] vs. 3.21 [2.85-3.46]) and corrected iCEB (QTc/QRS: 3.25 [2.91-3.73] vs. 3.49 [2.99-3.78]). Higher QRS dispersion was seen in type 1 subjects (QRSd: 34 [24-66] vs. 24 [12-34] ms) but QT dispersion (QTd: 48 [39-71] vs. 43 [22-94] ms), QTc dispersion (QTcd: 52 [41-79] vs. 46 [23-104] ms), JTpeak dispersion (44 [23-62] vs. 45 [30-62] ms), Tpeak - Tend dispersion (28 [15-34] vs. 29 [22-53] ms) or Tpeak - Tend/QT dispersion (0.06 [0.03-0.08] vs. 0.08 [0.04-0.12]) did not differ between the two groups. Type 1 subjects showed higher (QRSd x Tpeak - Tend)/QRS (25 [19-44] vs. 19 [9-30] ms) but similar iCEB dispersion (0.83 [0.49-1.14] vs. 0.61 [0.34-0.92]) and iCEBc dispersion (0.93 [0.51-1.15] vs. 0.65 [0.39-0.96]). Conclusion: Higher levels of dispersion in conduction and repolarization are found in type 1 than non-type 1 BrS patients, potentially explaining the higher incidence of ventricular arrhythmias in the former group.